(untitled) (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Attention-deficit hyperactivity disorder (ADHD) is a highly prevalent neurodevelopmental condition linked to imbalances in neurotransmitter systems. Zinc (Zn), an essential cofactor in these metabolic pathways, has been implicated in ADHD pathogenesis. Given the high prevalence of Zn deficiency in the region and a critical gap in local data, this study aimed to assess and compare serum Zn levels in children with ADHD versus age-matched healthy children in Bangladesh. Methods: This was a cross-sectional study conducted in Dhaka, enrolling a total of 60 children aged 4 to 12 years: 30 newly diagnosed children with ADHD (Case Group) and 30 apparently healthy controls (Control Group). Baseline characteristics of the two study groups encompassed age, body mass index (BMI), gender, maternal and obstetric history, family history of ADHD, maternal infection during pregnancy, low birth weight etc. Serum Zn levels were measured and were compared between the two study groups using the independent Sample t-Test. Results: The two groups were statistically comparable in terms of age and body mass index (BMI). However, the ADHD group exhibited a male predominance (p = 0.021) and a significantly higher rate of positive family history for the disorder (p = 0.011). The mean serum Zn level was significantly lower in the ADHD group (86.06 ± 17.64 µg/dl) compared to the control group (95.20 ± 15.91 µg/dl) (p = 0.032). While the average serum Zn levels were lower in the ADHD group for both males (86.9 ± 17.4 µg/dl) and females (80.5 ± 21.1 µg/dl) compared to their control counterparts (94.0 ± 14.1 µg/dl and 97.8 ± 18.1 µg/dl, respectively), these differences were not statistically significant in the individual gender subgroups (p = 0.159 for males, p = 0.133 for females). The study found no notable difference in serum Zn levels between preschool-age children (86.03 ± 17.82 µg/dl) and school-age children (86.08 ± 18.05 µg/dl) within the ADHD group (p = 0.995). Conclusion: Children with ADHD demonstrated significant deficiency in serum Zn compared to their healthy counterparts. However, this difference is not statistically significant when looking at males and females separately. Age (under or over 6 years) does not appear to affect zinc concentration within the ADHD group. These findings reinforce the biochemical link between Zn and ADHD and strongly suggest that routine micronutrient screening (particularly Zn) and targeted nutritional interventions may serve as beneficial ancillary strategies in the clinical management of children with ADHD. Ibrahim Cad Med J 2025, 15(1): 07-12